Crystal structure of the Campylobacter jejuni CmeC outer membrane channel. (6th May 2014) - Su, Chih‐Chia; Radhakrishnan, Abhijith; Kumar, Nitin; Long, Feng; Bolla, Jani Reddy; Lei, Hsiang‐Ting; Delmar, Jared A.; Do, Sylvia V.; Chou, Tsung‐Han; Rajashankar, Kanagalaghatta R.; Zhang, Qijing; Yu, Edward W.
Abstract As one of the world's most prevalent enteric pathogens, Campylobacter jejuni is a major causative agent of human enterocolitis and is responsible for more than 400 million cases of diarrhea each year. The impact of this pathogen on children is of particular significance. Campylobacter has developed resistance to many antimicrobial agents via multidrug efflux machinery. The CmeABC tripartite multidrug efflux pump, belonging to the resistance‐nodulation‐cell division (RND) superfamily, plays a major role in drug resistant phenotypes of C. jejuni. This efflux complex spans the entire cell envelop of C. jejuni and mediates resistance to various antibiotics and toxic compounds. We here report the crystal structure of C. jejuni CmeC, the outer membrane component of the CmeABC tripartite multidrug efflux system. The structure reveals a possible mechanism for substrate export.